Aneurysmal subarachnoid hemorrhage with concomitant posterior communicating artery fenestration. (1st February 2015) - Weiner, Gregory M.; Grandhi, Ramesh; Zwagerman, Nathan T.; Agarwal, Nitin; Friedlander, Robert M.
<x xml:space="preserve">Abstract</x> Fenestrations of the posterior communicating artery (PCoA) are extremely rare. Associated aneurysms have only been documented three times in the literature, and none associated with a subarachnoid hemorrhage. We describe a 52-year-old female who presented with a subarachnoid hemorrhage secondary to a ruptured saccular aneurysm at the proximal limb of a fenestrated right PCoA. The patient was also found to have bilateral middle cerebral artery (MCA) aneurysms. Surgical management included surmising the etiology of the subarachnoid hemorrhage with subsequent clipping of both the right PCoA and MCA aneurysm. The potential embryological mechanisms leading to a PCoA fenestration are discussed.